2013
DOI: 10.1021/jp404882t
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Methyl Radicals from Decomposition of Methyl-Substituted Silanes over Tungsten and Tantalum Filament Surfaces

Abstract: The formation of methyl radical from the decomposition of four methyl-substituted silane molecules, including monomethylsilane (MMS), dimethylsilane (DMS), trimethylsilane (TriMS), and tetramethylsilane (TMS), over tungsten and tantalum filament surfaces has been systematically studied using vacuum ultraviolet laser ionization mass spectrometry. The methyl radical intensity increases with temperature for both filaments in the low-temperature region; however, beyond the optimum temperature, a gradual decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 59 publications
7
23
0
Order By: Relevance
“…The similarity in the gas-phase chemistry when using DMS on the two filaments (Ta and W) is quite different from the observed difference in the Si radical formation 34 and deposited Si film properties 33 when using SiH 4 . Our previous study on the decomposition of methyl-substituted silanes, including DMS, on a metal surface 26 has shown that it is initiated by the same rate-limiting step, i.e., the cleavage of the Si-H bond, on both Ta and W filaments. The formation of H 2 occurs by the recombination reaction between two H adsorbates, following the Langmuir-Hinshelwood mechanism.…”
Section: Effect Of the Filament Materials On Dms Gas-phase Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in the gas-phase chemistry when using DMS on the two filaments (Ta and W) is quite different from the observed difference in the Si radical formation 34 and deposited Si film properties 33 when using SiH 4 . Our previous study on the decomposition of methyl-substituted silanes, including DMS, on a metal surface 26 has shown that it is initiated by the same rate-limiting step, i.e., the cleavage of the Si-H bond, on both Ta and W filaments. The formation of H 2 occurs by the recombination reaction between two H adsorbates, following the Langmuir-Hinshelwood mechanism.…”
Section: Effect Of the Filament Materials On Dms Gas-phase Chemistrymentioning
confidence: 99%
“…The mechanism for the formation of the H 2 molecule and the methyl radical from DMS along with other three methyl-substituted silane molecules has been discussed in detail in our previous work. 26 It has been shown that DMS dissociatively adsorbed on Ta and W filaments by Si-H bond cleavage. This is followed by Si-CH 3 bond breaking to form the methyl radical or by recombination of H adsorbates to form the H 2 molecule.…”
Section: Primary Decomposition On Ta and W Filamentsmentioning
confidence: 99%
“…This value was obtained under the collision-free conditions, where the reactions in the gas phase were not possible to occur. The dissociation of DSCB on the hot W surfaces follows a dissociative adsorption mechanism where the rate-determining step (RDS) is the initial Si-H bond rupture on the surface [7,21]. Due to the much higher pressures, the reactions in the HWCVD setup, that were studied in this work, are more complex involving both the heterogeneous reactions on the metal surfaces and the reactions in the gas phase.…”
Section: The Temperature Dependence Of the Rate Constants Of Dscb Decmentioning
confidence: 99%
“…The lack of hydrocarbon molecules with increasing pressure of MMS is probably due to the fact that free radicals do not participate in the gas-phase chemistry when using MMS, despite the fact that free radicals were detected from the study of the primary decomposition of MMS on the tantalum filament. 32,33 To support the conclusion that the dominant chemistry with MMS is not affected during secondary gas-phase reactions due to the absence of small hydrocarbons produced, experiments of MMS with the addition of ethene were conducted. These experiments will give us insights into the effect of the ethene presence on MMS chemistry if it was produced under our experimental conditions.…”
Section: Effect Of Source Gas Pressure On Mms Gas-phase Chemistrymentioning
confidence: 99%